Om Ordningen af Plovprøver samt en Beretning om en Plovprøve ved Hillerød d. 26de Sept. 1872. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Om Ordningen af Plovprøver samt en Beretning om en Plovprøve ved Hillerød d. 26de Sept. 1872.